Robust dynamic admission control for unified cell and call QoS in statistical multiplexers. - Mitra, D. (IEEE Journal on selected areas in communications)
The design of connection admission control (CAC) for a simple Markovian model of a multiservice statistical multiplexer is considered. The paper begins by laying the foundation through several fundamental analytic concepts, such as a semi-Markov decision process formulation of the design problem and time scale decomposition, before progressively leading up to real-world requirements, like robustness and simplicity of design. Several numerical illustrations are given. The salient contributions of the paper are as follows. (1) A unified treatment of multiclass cell and call QoS. (2) A CAC design which is robust, fair, and efficient. (3) Simplicity in the CAC design, together with an evaluation of the tradeoff with performance. (4) An analytic technique for computing the feasibility region in the space of call arrival rates where some control exists to satisfy QoS. (5) The discovery of near linearity of the boundary of the feasible region, which is then used to decompose the design problem. (6) A unified treatment of aggressive and conservative forms of CAC, the latter being conventional and the former yielding better call level performance. (7) An effective bandwidth definition based on the aggressive form of CAC, which influences the CAC design. (8) A demonstration of the beneficial impact on performance of cell level control. (9) An asymptotic theory of the joint behavior of cell loss and call blocking. (10) A rigorous development of time scale decomposition. (11) A numerical evaluation of the accuracy of the notion of nearly completely decomposable Markov chains